The Relationship Between Graduates’ Perceived Tension Before the Exams and Their Temperament and Engagement in School Activities - Zinkevičius, Deimantas; Nasvytienė, Dalia (Pedagogika, 2023)
Maturity exams are important for graduates, as they determine the opportunities for further learning and career choice. Students differently respond to knowledge tests, but for many of them, this puts a lot of tension. The tension experienced in approaching final exams can depend on many personal and situational factors. This study aimed to investigate the relationships between graduates’ perceived tension before the exams, which consists of test anxiety with fear appeals, and characteristics of their temperament as well as engagement in school activities. The 128 participants 18-19-year-old graduates, 99 girls and 29 boys, from 35 Lithuanian gymnasiums, participated in the study. Respondents completed several instruments during the study: FRIEDBEN Test Anxiety Scale, Teachers’ Use of Fear Appeals Questionnaire, The Adult Temperament Questionnaire, and School Engagement Questionnaire. The results showed that graduates’ test anxiety is positively associated with fear appeals, is predicted by negative affectivity, and negatively related to effortful control; no clear ties between test anxiety and extraversion, engagement in school activities.